2016
DOI: 10.1037/a0039095
|View full text |Cite
|
Sign up to set email alerts
|

A multilevel analysis of school climate, homophobic name-calling, and sexual harassment victimization/perpetration among middle school youth.

Abstract: Objective: Using multiinformant, multilevel modeling, this study examines the association between teacher/staff perceptions of school environment and student reports of homophobic name-calling and sexual harassment. Method: Surveys were conducted with 1,447 teachers/staff and 3,616 6th grade students across 36 middle schools in the Midwest. Results: Bivariate associations revealed that when teachers perceive schools as committed to bullying prevention, students reported less homophobic name-calling perpetratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 42 publications
(75 reference statements)
1
50
1
8
Order By: Relevance
“…Much less is known about how modifiable contextual factors, such as school‐level student‐teacher relationships, are related to bullying involvement, although emerging evidence indicates this may be a fruitful avenue for investigation . In a notable exception, Rinehart and Espelage found that school‐level attitudes about gender equity and staff/administration commitment to bullying prevention were associated with lower levels of prejudice‐based harassment among middle school students.…”
Section: School‐level Context and Student Behaviormentioning
confidence: 99%
“…Much less is known about how modifiable contextual factors, such as school‐level student‐teacher relationships, are related to bullying involvement, although emerging evidence indicates this may be a fruitful avenue for investigation . In a notable exception, Rinehart and Espelage found that school‐level attitudes about gender equity and staff/administration commitment to bullying prevention were associated with lower levels of prejudice‐based harassment among middle school students.…”
Section: School‐level Context and Student Behaviormentioning
confidence: 99%
“…Among 722 high school students (55% female, 87% white, 86% heterosexual), 66.8% had observed at least one instance of homophobic behavior in the past 30 days (Poteat and Vecho 2015). Further, because these epithets are often exchanged within peer groups, homophobic name-calling perpetration and victimization are highly correlated ( r = .70; Rinehart and Espelage 2016) and often co-occur (Poteat and Espelage 2005). …”
Section: Introductionmentioning
confidence: 99%
“…In addition to directly intervening during and after situations of RA and SA, found that school personnel discussed ways they could proactively take action (e.g., talking with teens about healthy relationships) even in the absence of RA and SA. This finding is especially promising given that researchers have found that greater demonstrations of gender equity and intolerance of sexual harassment among school personnel were associated with lower rates of self-reported SA and sexual harassment victimization and perpetration among middle school students (Espelage, Polanin, & Low, 2014;Rinehart & Espelage, 2016). Additionally, other research that has focused specifically on school personnel's reactions to bullying among middle and high school youth has found that (a) school personnel are more likely to provide youth with educational information on bullying than to directly intervene in bullying situations (Novick & Isaacs, 2010); (b) school personnel who felt prepared to take action in youth bullying situations were more likely to take action in real bullying situations than school personnel who did not feel prepared to do so (Novick & Isaacs, 2010); and (c) youth are more likely to seek help from teachers who were seen as effective and fair in the action they took to address bullying among teens (Aceves, Hinshaw, Mendoza-Denton, & Page-Gould, 2010).…”
Section: O R I G I N a L A R T I C L Ementioning
confidence: 91%